HIV incidence and associated risk factors in female spouses of men who inject drugs in Pakistan - Jenny Iversen; Salman ul H Qureshi; Malika Zafar; Machteld Busz; Lisa Maher (BMC, 2021)
Abstract Introduction Female sexual partners of men who inject drugs (MWID) living with HIV are at risk of HIV transmission. HIV prevalence estimates among non-drug using female sex partners of MWID are scarce, with no studies documenting HIV incidence. We investigated HIV prevalence and incidence among female spouses of MWID registered at Nai Zindagi Trust (NZT), Pakistan, between 2012 and 2019. Methods NZT registration and service provision data for female spouses who participated in HIV testing and counselling calculated HIV prevalence and incidence using the person years (PY) method. Cox proportional hazards models identified factors associated with incident infection. Results Overall HIV prevalence among female spouses of MWID was 8.5%. Among 3478 HIV-negative female spouses, 109 incident infections were observed, yielding an incidence rate of 1.5/100PY (95% CI 1.2-1.8). Independent predictors of incident infection were registration in Punjab province (AHR 1.73 95% CI 1.13-2.68, p = 0.012) and 1-5 years of education (AHR 1.89 95% CI 1.22-2.93, p = 0.004). Knowledge of HIV at registration was protective against infection (AHR 0.51, 95% CI 0.26-0.99, p = 0.047), along with a MWID spouse who had initiated antiretroviral therapy (ART) (AHR 0.25, 95% CI 0.16-0.38, p < 0.001), while incident infection was inversely associated with number of children (≥ 5 children AHR 0.44 95% CI 0.22-0.88, p = 0.022). Conclusions Additional efforts are needed to reduce HIV transmission among female spouses of MWID, including targeted provision of HIV education and access to HIV screening. Interventions that target MWID are also required, including evidence-based drug treatment and access to ART, including support to maximize adherence. Finally, consideration should be given to making HIV pre-exposure prophylaxis available to female spouses at high risk of HIV transmission, particularly young women and those whose husbands are not receiving, or have difficulty adhering to, ART.